STRATEGI PENERAPAN KUALITAS PELAYANAN JASA SEBAGAI UPAYA PENINGKATAN KEPUASAN LAYANAN PADA KANTOR DINAS PENDAPATAN DAERAH PALEMBANG - R, Ike Kusdyah (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstract: The purpose of this study is to determine and analyze whether there is a simultaneous influence of variables of service quality (responsiveness, reliability, tangible, assurance and emphaty) to the satisfaction of compulsory motor vehicle taxes on the Provincial Revenue Office of Palembang in South Sumatra and to know and analyze in partial variables of service quality (responsiveness, reliability, tangible, assurance and emphaty) to the satisfaction of compulsory motor vehicle taxes on the Provincial Revenue Office of Palembang in South Sumatra. This type of research is a causal explanative (Explanatory research) is the research that aims to explain the influence of several variables or relations as for the object of this study are all taxpayers in the office Samsat Palembang and the sample set of 100 samples. By using a accidental sampling. The model analysis was used to prove the hypothesis with multiple regression analysis, with test F and test t. The results with adjusted R square of 0982, that the Tangible (X1), Reliability (X2) Responsiveness (X3), Assurance (X4) and Emphaty (X5) is able to explain and have a strong relationship for 98.2% of the taxpayer to the satisfaction (Y ), while the rest is explained by other variables not included in this study. The seventh hypothesis proposed significantly influence the dependent variable. Where Tangible (X1), Reliability (X2) Responsiveness (X3), Assurance (X4) and Emphaty (X5) simultaneously significant effect on the satisfaction of the taxpayer (Y) either partially or simultaneously. Keywords: Service Quality, Satisfaction